Impact of intravesical Bacillus Calmette-Guérin and chemotherapy on the bladder microbiome in patients with non-muscle invasive bladder cancer - James, Christopher; Gomez, Kayeromi; Desai, Shalin; Patel, Hiten D.; Rac, Goran; Doshi, Chirag P.; Dornbier, Ryan; Bajic, Petar; Halverson, Thomas; Gupta, Gopal N.; Quek, Marcus L.; Gorbonos, Alex; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
ABSTRACT Introduction: Intravesical therapy (IVT), including Bacillus Calmette-Guérin (BCG), is the standard of care for high grade (HG) non-muscle invasive bladder cancer (NMIBC). Despite the use of IVT, many patients recur after treatment. The bladder microbiome and its role in disease processes has recently risen to prominence. We aim to characterize changes that occur in the bladder microbiome over the course of IVT and assess whether these changes correlate with outcomes in patients with NMIBC. Methods: Patients with NMIBC undergoing induction BCG or IVT were prospectively enrolled from January 2019 to March 2020. Patients with clinical T2 or greater pathology or active urinary tract infection at enrollment were excluded. Twenty-nine patients had catheterized (bladder) urine samples collected prior to induction intravesical therapy and prior to each IVT instillation. Twenty-seven received BCG while 2 received intravesical gemcitabine. Bacteria were identified using 16S ribosomal RNA gene sequencing. Bladder microbiome changes were evaluated and differences between patients who recurred and patients who did not recur after IVT were investigated. Results: Across the 29 patients analyzed, bacterial richness decreased significantly following intravesical therapy (Richness, P=0.01). In contrast, evenness and overall diversity did not change significantly (Pielou, P=0.62; Shannon, P=0.13). Patients who experienced recurrence had a higher relative abundance of Aerococcus in their urine (P<.01), while those who did not recur had significantly more Ureaplasma (P=0.01) and Escherichia/Shigella species (P=0.05). Patients with decreased levels of alpha diversity were more likely to fall within the non-recurrence cohort. Conclusions: IVT for NMIBC appears to change the urinary microbiome by decreasing richness while not altering evenness or overall diversity. The presence of Aerococcus species may be predictive of a poor cancer response to IVT, while the presence of Ureaplasma and Escherichia/Shigella may predict a favorable response to IVT. Further studies are warranted to elucidate and confirm the significance of changes in the bladder microbiome.